EFEK SINTESIS SILANE COUPLING AGENT PADA SIFAT FISIS DAN MEKANIS KOMPOSIT DENGAN PENGISI SERBUK KENAF DAN RESIN EPOKSI - Delovita Ginting; Reka Nuansa Fitri (Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to see the effectiveness of the chemical treatment of silane coupling agent on the physical properties (density and water absorption) and mechanical properties (tensile strength and impact strength) of the kenaf powder composite. Kenaf powder was alkalized using NaOH for 4 hours, then mashed using a grinding machine until it passed a 50 mesh sieve. The kenaf powder that has passed the sieve is then chemically treated with a silane coupling agent solution. Variations in the concentration of the silane coupling agent solution used were 0%, 10%, 20% and 30% of the mass of kenaf powder. Kenaf powder which has been synthesized with a silane coupling agent is then mixed with epoxy resin adhesive with a ratio of 30/70 in weight percent. The composite compaction process uses a Hydrolic Hot Press compacting machine with a pressure of 20 Bar at a temperature of 125 oC and a holding time of 15 minutes. The result of this research is that the treatment with 20% silane coupling agent on kenaf powder is effective in improving the physical and mechanical properties of the composite.